Increasing Teacher Work Productivity through Strengthening Organizational Culture, Interpersonal Communication, Tasks Interdependence, Job Satisfaction and Work Motivation - Siregar, Uli Rohana; Hermawan, Andi; Setyaningsih, Sri (Universitas Muhammadiyah Sumatera Utara (UMSU), 2024)
Work productivity is the potential or power produced by individuals which is used to achieve maximum results to achieve effective and quality output. Based on preliminary research, it is known that the work productivity of teachers at PGRI Vocational Schools in Bogor Regency needs to be increased in order to achieve educational goals. Therefore, research is needed to obtain information on variables related to increasing work productivity. The aim of this research is to carry out strategies and ways to increase work productivity by conducting research on the influence of organizational culture variables, interpersonal communication, task interdependence, job satisfaction and work motivation. This research uses the path analysis method to determine the influence between the variables studied and the SITOREM method for indicator analysis in order to obtain optimal solutions in an effort to increase work productivity.